Firefighters and the liver: Exposure to PFAS and PAHs in relation to liver function and serum lipids (CELSPAC-FIREexpo study) - Pálešová, Nina; Maitre, Léa; Stratakis, Nikos; Řiháčková, Katarína; Pindur, Aleš; Kohoutek, Jiří; Šenk, Petr; Bartošková Polcrová, Anna; Gregor, Petr; Vrijheid, Martine; Čupr, Pavel (International journal of hygiene and environmental health, 2023)
INTRODUCTION: Firefighting is one of the most hazardous occupations due to exposure to per- and polyfluoroalkyl substances (PFAS) and polycyclic aromatic hydrocarbons (PAHs). Such exposure is suspected to affect the cardiometabolic profile, e.g., liver function and serum lipids. However, only a few studies have investigated the impact of this specific exposure among firefighters. METHODS: Men included in the CELSPAC-FIREexpo study were professional firefighters (n = 52), newly recruited firefighters in training (n = 58), and controls (n = 54). They completed exposure questionnaires and provided 1-3 samples of urine and blood during the 11-week study period to allow assessment of their exposure to PFAS (6 compounds) and PAHs (6 compounds), and to determine biomarkers of liver function (alanine aminotransferase (ALT), gamma-glutamyl transferase (GGT), aspartate aminotransferase (AST), alkaline phosphatase (ALP) and total bilirubin (BIL)) and levels of serum lipids (total cholesterol (CHOL), low-density lipoprotein cholesterol (LDL) and triglycerides (TG)). The associations between biomarkers were investigated both cross-sectionally using multiple linear regression (MLR) and Bayesian weighted quantile sum (BWQS) regression and prospectively using MLR. The models were adjusted for potential confounders and false discovery rate correction was applied to account for multiplicity. RESULTS: A positive association between exposure to PFAS and PAH mixture and BIL (β = 28.6%, 95% CrI = 14.6-45.7%) was observed by the BWQS model. When the study population was stratified, in professional firefighters and controls the mixture showed a positive association with CHOL (β = 29.5%, CrI = 10.3-53.6%) and LDL (β = 26.7%, CrI = 8.3-48.5%). No statistically significant associations with individual compounds were detected using MLR. CONCLUSIONS: This study investigated the associations between exposure to PFAS and PAHs and biomarkers of cardiometabolic health in the Czech men, including firefighters. The results suggest that higher exposure to a mixture of these compounds is associated with an increase in BIL and the alteration of serum lipids, which can result in an unfavourable cardiometabolic profile.
Keywords: polycyklické aromatické uhlovodíky; játra; Occupational Exposure; per- and polyfluoroalkyl substances/PFAS; kardiovaskulární nemoci; Humans; Polycyclic aromatic hydrocarbons/PAHs; lipidy; lidé; Polycyclic Aromatic Hydrocarbons; Biomarkers; hasiči; Mixture analysis; biologické markery; Liver; Cardiovascular Diseases; Male; pracovní expozice; Lipids; Bayesova věta; Occupational exposure; Firefighters; Liver function; fluorokarbony; mužské pohlaví; Fluorocarbons; Bayes Theorem